RETHINKING RIFFAT HASSAN'S THOUGHTS: BETWEEN ISLAM, GENDER, AND EQUAL RIGHTS - Fadilah, Alniatul; Syihabuddin, Muhammad; Manggala, Kayan; Aulia, Firza Nada (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
There are many statements that men and women are different in all respects in the name of religion, especially Islam. Such reductions need to be re-examined so that there are no misperceptions that cause chaos and misinterpretation. With that, through the thought of Riffat Hassan as a foothold, Islam is very merciful to differences. Like the nature of men and women, both of which have the same potential in showing existence. It is necessary to consider and negotiate Riffat Hassan's thoughts on equality between men and women. Three main key points; the first is that equality is more important than others, the second is the concept of polygamy which is not necessarily interpreted as letter leg, and the third is the concept of veil or purdah which has many interpretations. Thus, through the study of Riffat Hassan's thoughts, it can be summarized that; everything departs from God's justice that does not discriminate against his servants because the main thing in God's eyes is the devotion of his servants.